534 WHICH IS THE BEST SURGICAL MANAGEMENT OF GASTROESOPHAGEAL REFLUX DISEASE (GERD) IN PATIENTS WITH SYSTEMIC SCLEROSIS WITH PULMONARY INVOLVEMENT?. (14th September 2020) - Szachnowicz, S; Marques, F; Duarte, A; Bianchi, E; Nasi, A; Queiroz, N; Seguro, F; Sallum, R; Cecconello, I
Abstract: : Systemic sclerosis (scleroderma) is frequently associated with both gastroesophageal reflux disease (GERD) and simultaneous esophageal dysmotility (ED). Antireflux surgery have to considerate the individual esophageal dysmotility degree of each patient. They need GERD treatment as a priority to help control worsening lung function, in patients developing pulmonary fibrosis or in lung transplantation patients. Another issue is the possibility that fundoplications in this patients can cause esophageal stasis, an event that can also disrupt lung function. Methods: 113 patients were referred for surgical treatment of GERD, related with pulmonary impairment. SS patients are the most critical, once the ED may be an obstacle to fundoplication. We divided this patients in three groups regarding the esophageal function. A- Partial fundoplication—without important affection of ED, checked by manometry, confirmed with a complete emptying of esophagus in barium swallow test. B- Laparoscopic gastric bypass for treatment of GERD (RYGBP)—aperistalsis or atonic esophageal body, with normal esophageal empty at barium test. C- Esophagectomy—Atonic esophageal body with important delayed emptying of esophagus in barium swallow test. Results: We could follow up 4 patients in group A, 3 patients in group B and 2 patients in group C. Median follow-up was 75, 30 and 18 months for Groups A, B and C respectively. All 3 patients in the RYGB group resolved all the symptoms including heartburn and regurgitation, with a sensitive improve in lung function. Only 1 patients in the fundoplication group reported symptom improvement or resolution. The Patients at Group C have no complain of Dysphagia but referred regurgitation and difficulty feedingtill first year. Conclusion: Laparoscopic RYGB as an anti-reflux procedure is safe and may provide an alternative to fundoplication in the treatment of GERD for systemic sclerosis patients with esophageal dysmotility. Both reflux control and dysphagia rates were improved in the RYGBP group compared with fundoplication and esophagectomy.. This finding suggests that RYGBP may be an option for the primary manage- ment of scleroderma-associated gastroesophageal reflux in patients without importnat impairing of esophageal emptying.